Optimasi Sintesa Ester Maltitol Asam Lemak Dari Minyak Kelapa Sawit Menggunakan Lipase Getah Pepaya sebagai Katalisator - Ratri Retno Utami; Alfrida Lullung (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Research optimization of the ester Maltlitol Fatty Acid (EMALTAL) synthesis from palm as biosurfactant has been conducted. Papaya latex lipase used as a catalyst in the synthesis. This research aims to study the optimization of biosurfactant synthesis Maltitol Fatty Acid Esters (EMALTAL) from palm oil using papaya latex lipase as a catalyst. Before the synthesis carried out, palm oil is converted into methyl esters Fatty Acids (EMAL). Optimal conditions needed to form EMALTAL determined by Response Surface Method / RSM. To get the optimum conversion EMALTAL synthesis, the reaction is affected by three variables: time, papaya latex lipase levels and temperature as well as the response variable is called the optimum conversion EMALTAL synthesis. By using response surface methods (RSM), the optimal synthesis conditions obtained at a temperature of 0C 39.4490, 53.2440 minutes of time and concentration of crude papaya latex 7.6600% to 28.6806% conversion of surfactant in the form of monoester. Characterization of EMALTAL shows the melting point of 24.5-27oC, 180oC smoke point and refractive index of 1.441. EMALTAL produced a monoester that serves as an emulsifier